2011
DOI: 10.1371/journal.pone.0028408
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Signature of Spina Bifida Risk from Pathway-Informed Comprehensive Gene-Variant Analysis

Abstract: Despite compelling epidemiological evidence that folic acid supplements reduce the frequency of neural tube defects (NTDs) in newborns, common variant association studies with folate metabolism genes have failed to explain the majority of NTD risk. The contribution of rare alleles as well as genetic interactions within the folate pathway have not been extensively studied in the context of NTDs. Thus, we sequenced the exons in 31 folate-related genes in a 480-member NTD case-control population to identify the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…If histone methylation perturbation were the cause of NTDs, the common A222V allele of MTHFR might cause altered histone methylation. A more comprehensive evaluation of genetic variants of all genes affecting folate metabolism has provided a stronger link to NTDs than previously reported and is also consistent with a mechanism rooted in chromatin modification (Marini et al 2011).…”
Section: Human Diseasesupporting
confidence: 80%
“…If histone methylation perturbation were the cause of NTDs, the common A222V allele of MTHFR might cause altered histone methylation. A more comprehensive evaluation of genetic variants of all genes affecting folate metabolism has provided a stronger link to NTDs than previously reported and is also consistent with a mechanism rooted in chromatin modification (Marini et al 2011).…”
Section: Human Diseasesupporting
confidence: 80%
“…Last, but not least, between‐study heterogeneity, which must be considered with attention, existed in both overall and subgroup analyses. The heterogeneity among individual studies, as we mentioned above, had various origins, among which the ethnic variations might play a crucial role as differences in folic acid pathway risk profiles have recently been reported between Hispanics and non‐Hispanic whites (Marini et al,2011), but we could not separate Hispanics out for most of the included studies that barely distinguished between these two ethnic groups.…”
Section: Discussionmentioning
confidence: 96%
“…In our meta-analysis, we extracted data from 9 relevant articles [1,[8][9][10][15][16][17][18][19]; they were all selected through a pre-specified search strategy. Quality assessment for the overall studies was shown with a bar graph according to the Newcastle-Ottawa Scale tool in Fig.…”
Section: Meta-analysis Of the Association Between 1958gn A And Ntd Riskmentioning
confidence: 99%
“…Neural tube defect (NTD) is among the most common and deadly human congenital malformations at birth and manifested as a wide range of phenotypes, primarily including anencephaly, spina bifida and encephalocele which result from failure of the neural tube to close properly in the developing brain or lower spine [1,2]. The incidence rate of NTD is about 0.2% worldwide, but this rate varies in different races and sections with a conspicuous diversity which may be a result of genetic diversity [3].…”
Section: Introductionmentioning
confidence: 99%